KPT‐330 and Y219 exert a synergistic antitumor effect in triple‐negative breast cancer through inhibiting NF‐κB signaling. Issue 4 (20th March 2023) - Wen, Tiantian; Geng, Mengzhu; Bai, Enhe; Wang, Xueyuan; Miao, Hang; Chen, Zhimeng; Zhou, Hui; Wang, Jia; Shi, Jingmiao; Zhang, Yin; Lei, Meng; Zhu, Yongqiang
Abstract : Triple‐negative breast cancer (TNBC) is an aggressive breast cancer subtype, which has poor prognosis due to the lack of effective targeted drugs. KPT‐330, an inhibitor of the nuclear export protein CRM‐1, has been widely used in clinical medicine. Y219, a novel proteasome inhibitor designed by our group, shows superior efficacy, reduced toxicity, and reduced off‐target effects as compared to the proteasome inhibitor bortezomib. In this study, we investigated the synergistic effect of KPT‐330 and Y219 against TNBC cells, as well as the underlying mechanisms. We report that combination treatment with KPT‐330 and Y219 synergistically inhibited the viability of TNBC cells in vitro and in vivo . Further analysis revealed that the combined use of KPT‐330 and Y219 induced G2‐M phase arrest and apoptosis in TNBC cells, and attenuated nuclear factor kappa B (NF‐κB) signaling by facilitating nuclear localization of IκB‐α. Collectively, these results suggest that the combined use of KPT‐330 and Y219 may be an effective therapeutic strategy for the treatment of TNBC. Abstract : We investigated the synergistic effect of KPT‐330 and Y219 against TNBC cells, as well as the underlying mechanisms. Combining KPT‐330 and Y219 induced G2‐M phase arrest and apoptosis in TNBC cells, and attenuated NF‐κB signaling by facilitating nuclear localization of IκB‐α. These results suggest that combining KPT‐330 and Y219 may be an effective therapeutic strategy for treating TNBC.